Examining media reports of pediatric unintentional firearm injury deaths for prevention messaging concerning secured storage of firearms: U.S., 2021-2022 - Bart Hammig; Abigail Bordelon; Corinne Chandler (BMC, 2024)
Abstract Background Media outlets that report on firearm injuries and deaths may provide an important role in emphasizing safe storage practices, particularly when unintentional firearm injuries and deaths occur among young children. There has been a scarcity of research on aspects of media reports on injuries, particularly concerning prevention messaging. The objective of the present study was to examine prevention messaging on the safe storage of firearms among media outlets when reporting on unintentional firearm injury deaths among children aged 0-11. Methods The Gun Violence Archive collects information from media sources regarding firearm injuries and deaths. We analyzed data from 2021 to 2022 to analyze prevention messaging incorporated into the media reports. We then examined if media reporting of events that occurred in States with child access prevention (CAP) laws had a higher likelihood of including prevention messaging compared to those events occurring in States without CAP laws. Results There were 223 deaths reported that were attributed to unintentional firearm discharge among children aged 0-11. Prevention messages were delivered in 61 of the 223 incidents. Specific messages which included the word "lock" when referring to firearm storage were included in 21.9% of all incidents. An analysis examining State CAP laws and the presence of any prevention message per event did not yield any discernable relationship. Conclusion Inclusion of prevention messaging stating that firearms should be stored locked and unloaded when reporting on unintentional firearm injury deaths among children is lacking. When specific prevention messaging was included, the source was often law enforcement. Public health officials may play an important role in educating the journalistic and law enforcement communities about the inclusion of safe storage messages when reporting on firearm deaths.